Upaya Pemberian Kredit Terhadap Peningkatan Pendapatan Usaha Mikro Kecil : (Studi Kasus Koperasi Kredit Simpan Pinjam Gaharu Ende) - Damianus Tola (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
This research aim to know: how credit increase the micro business on Ende Gaharu Union. This research use descriptive statistic as its method, The result tells that there are 40 research instruments–which consist of 20 (x) questions of variable and 20 (y) questions of variable—that shows an impact of credit given on the increasing of micro business income on Gaharu Ende Credit Union as 88,9%. The impact of credit given on the increasing of micro business is positive. This is depicted through the impact of credit given on the increasing of micro business income as 88,9% and 11,1% careless factors. The testing of the effort on giving credit on micro business has touched a good phase on prospering the micro business in Ende. Thus, creditors have to pay their credit punctually for the continuity of micro business. Besides, the union members need to save as well in order to increase the prosperity.